(untitled) - Steiner, Erich (Oxford, 1996)
This book is a comprehensive textbook of mathematics for chemistry students. All the most usefull and important topics are covered, with numerous examples of applications in chemistry, and some in physics. Several topics such as the differential equations of chemical kinetics and quantum chemistry are discussed in considerable detail.
Keywords: Chemistry; Mathematics